2009
DOI: 10.1007/s00383-009-2419-6
|View full text |Cite
|
Sign up to set email alerts
|

Congenital midline cervical cleft with an underlying bronchogenic like cyst

Abstract: Congenital midline cervical cleft (CMCC) is an uncommon malformation. We report a case of a baby girl aged 3 days with a CMCC associated with a cyst reported as a bronchogenic cyst (BC). The pathology is not specific. The association of BC and CMCC is extremely rare and only five cases have been found in the literature. We report our case and review the relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In their retrospective case series of 8 patients, Achard et al [17] found only one patient with an atrophic kidney. Some authors found that CMCC can be associated with other anomalies like thyroglossal duct cyst [21], bronchogenic cyst [22], or a midline cleft from mandible to sternum [23].…”
Section: Discussionmentioning
confidence: 99%
“…In their retrospective case series of 8 patients, Achard et al [17] found only one patient with an atrophic kidney. Some authors found that CMCC can be associated with other anomalies like thyroglossal duct cyst [21], bronchogenic cyst [22], or a midline cleft from mandible to sternum [23].…”
Section: Discussionmentioning
confidence: 99%
“…10 The midline cervical cleft may be a solitary deformity, but there are cases where it is combined with thyroglossal duct cyst, ectopic bronchogenic cyst, branchial cyst, midline hemangioma, ectopia cordis, cleft lip, mandible or tongue, cleft sternum, absence of hyoid bone or thyroid cartilage, or congenital heart disease. 7,11,12 This eventually results in a fourth clinical issue, failure of diagnosis of any of these disorders. 1 Different theories have been proposed on the embryological origin of the CMCC.…”
Section: Discussionmentioning
confidence: 99%
“…The midline cervical cleft may be a solitary deformity, but there are cases where it is combined with thyroglossal duct cyst, ectopic bronchogenic cyst, branchial cyst, midline hemangioma, ectopia cordis, cleft lip, mandible or tongue, cleft sternum, absence of hyoid bone or thyroid cartilage, or congenital heart disease [9, 12, 16]. This eventually results to a fourth clinical issue, failure of diagnosis of any of these disorders [1].…”
Section: Discussionmentioning
confidence: 99%